2012
DOI: 10.1080/13670050.2012.676620
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heritage language instruction on first language proficiency: a psycholinguistic perspective

Abstract: This study investigates the effects of weekly heritage language (HL) classes on first language (L1) proficiency in speakers who arrived in the second language (L2)-dominant setting before the onset of puberty. Two groups of L1 Spanish Á L2 Swedish bilingual high school students living in Sweden participated in the study. One group currently attended HL classes once a week, whereas the other group was no longer doing so. The two groups did not differ with regard to the total number of years of HL class attendan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 44 publications
1
8
0
4
Order By: Relevance
“…Besides extending the domain of inquiry to different features in other bilingual populations, an additional avenue for future research on L1 attrition is in the role of L1 education, the only background variable besides L1 exposure that was observed to have an effect on attrition in the present study. This effect of L1 education (wherein more education was associated with a lower likelihood of perceptual attrition) converges with other research that had investigated domains other than speech perception (Bylund & Díaz, 2012;Hakuta & D'Andrea, 1992). However, whereas Bylund and Díaz suggested that the effects of L1 education are short term (i.e., do not persist long after the end of L1 education), we found consistent effects of L1 education even with a participant sample that included several individuals who were not currently engaged in a L1 educational experience.…”
Section: Limitations and Future Studysupporting
confidence: 87%
“…Besides extending the domain of inquiry to different features in other bilingual populations, an additional avenue for future research on L1 attrition is in the role of L1 education, the only background variable besides L1 exposure that was observed to have an effect on attrition in the present study. This effect of L1 education (wherein more education was associated with a lower likelihood of perceptual attrition) converges with other research that had investigated domains other than speech perception (Bylund & Díaz, 2012;Hakuta & D'Andrea, 1992). However, whereas Bylund and Díaz suggested that the effects of L1 education are short term (i.e., do not persist long after the end of L1 education), we found consistent effects of L1 education even with a participant sample that included several individuals who were not currently engaged in a L1 educational experience.…”
Section: Limitations and Future Studysupporting
confidence: 87%
“…Despite all of these above-mentioned limitations, studies have shown that participation in MTI has a positive impact on students' language and literacy competencies in the minoritised language (e.g. Bylund and Diaz 2012;Ganuza and Hedman 2017a), and on their school achievements in general (e.g. Ganuza and Hedman, forthcoming;Skolverket 2008).…”
Section: Mth In Swedenmentioning
confidence: 99%
“…High-quality bilingual education programs, where the HL is an official school language together with German, are rare. Bylund and Díaz (2012) analyzed the effect of HL instruction on HSs language proficiency in similar extracurricular HL classes in Sweden and concluded that these courses have a positive effect on HL proficiency but noted also that these effects are not longlasting. HSs who no longer attend HL classes are outperformed by HSs enrolled in these courses.…”
Section: The Role Of Heritage Language Instructionmentioning
confidence: 99%